Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.15430/jcp.2016.21.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract ofCirsium japonicumvar.ussurienseKitamura Exhibits the Activation of Nuclear Factor Erythroid 2-Related Factor 2-dependent Antioxidant Response Element and Protects Human Keratinocyte HaCaT Cells Against Oxidative DNA Damage

Abstract: Keratinocytes are constantly exposed to extracellular insults, such as ultraviolet B, toxic chemicals and mechanical stress, all of which can facilitate the aging of keratinocytes via the generation of intracellular reactive oxygen species (ROS). Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that plays a critical role in protecting keratinocytes against oxidants and xenobiotics by binding to the antioxidant response element (ARE), a cis-acting element existing in the promoter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The human keratinocyte cells (HaCaT) were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA). HaCaT and HaCaT-ARE (stably transfected with 3xARE-luciferase gene) [ 23 ] cells were maintained at 37 °C in a humidified atmosphere of 5% CO 2 /95% air in RPMI1640 supplemented with 10% heat-inactivated FBS and 50 U/mL penicillin/streptomycin mixture (Invitrogen, Carlsbad, CA, USA). MCR was kindly provided by Dr. Heejung Yang of the Kangwon National University.…”
Section: Methodsmentioning
confidence: 99%
“…The human keratinocyte cells (HaCaT) were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA). HaCaT and HaCaT-ARE (stably transfected with 3xARE-luciferase gene) [ 23 ] cells were maintained at 37 °C in a humidified atmosphere of 5% CO 2 /95% air in RPMI1640 supplemented with 10% heat-inactivated FBS and 50 U/mL penicillin/streptomycin mixture (Invitrogen, Carlsbad, CA, USA). MCR was kindly provided by Dr. Heejung Yang of the Kangwon National University.…”
Section: Methodsmentioning
confidence: 99%
“…Chinese physicians usually use CH to treat hemorrhage, hypertension, and hepatitis. Recent pharmacological reports indicated that CH exhibits various pharmacological activities such as hemostatic, hepatoprotective, antidiabetic, anti-inflammatory, antibacterial, and sedative activities [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Due to its taxonomy (Asteraceae family) and morphology being similar to Silybum marianum (L.) Gaertn.…”
Section: Introductionmentioning
confidence: 99%
“…The aerial parts of this plant are used in oriental medicine as a diuretic, tonic, neuralgia stomachic, antiphlogistic, and detoxicant and have demonstrated hepatoprotective, anti-inflammatory, antitumor, antimutagenic, cytotoxic, and antioxidant effects in pharmacologic studies. [ 9 10 12 ] Flavonoids are reported to be major constituents of C. japonicum var. ussuriense .…”
Section: Resultsmentioning
confidence: 99%
“…ussuriense have reported hepatoprotective, anti-inflammatory, antitumor, antimutagenic, elimination, and antioxidant effects. [ 9 10 11 12 ] Polyacetylene and flavonoid have been reported as major constituents of C. japonicum var. ussuriense .…”
Section: Introductionmentioning
confidence: 99%